2003
DOI: 10.1038/sj.bjp.0705219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the neutral endopeptidase inhibitor thiorphan on cardiovascular and renal function in cirrhotic rats

Abstract: 1 Cirrhosis is associated with cardiovascular and renal dysfunction including sodium retention. Many vasoactive peptides such as atrial natriuretic peptide (ANP) and endothelin-1 (ET-1) are degraded by neutral endopeptidase 24.11 (NEP). We investigated the hemodynamic and renal effects of thiorphan, a NEP inhibitor, in a rat cirrhosis model. 2 Cirrhosis was induced by chronic bile duct ligation, and controls had sham operation. Systemic and renal hemodynamics in conscious, restrained animals were determined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
9
0
2
Order By: Relevance
“…Thus these studies stress that a successful natriuretic effect of ANP in the cirrhotic patient depends on suppression of antinatriuretic systems. Other possible mechanisms of ANP resistance could be diminished delivery of sodium to the ANP-sensitive part of the nephron (1, 26); increased renal neutral endopeptidase activity, limiting access of ANP to receptor sites (30); and alteration in renal ANP receptor density or function with a higher ratio of clearance receptors to biologically active receptors (11). We did not determine intrarenal levels of cGMP after sildenafil, and therefore a relative insensitivity of cellular pathways distal to cGMP could potentially also have contributed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus these studies stress that a successful natriuretic effect of ANP in the cirrhotic patient depends on suppression of antinatriuretic systems. Other possible mechanisms of ANP resistance could be diminished delivery of sodium to the ANP-sensitive part of the nephron (1, 26); increased renal neutral endopeptidase activity, limiting access of ANP to receptor sites (30); and alteration in renal ANP receptor density or function with a higher ratio of clearance receptors to biologically active receptors (11). We did not determine intrarenal levels of cGMP after sildenafil, and therefore a relative insensitivity of cellular pathways distal to cGMP could potentially also have contributed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the NEP-inhibitor thiorphan did not alter systemic vascular resistance in cirrhotic rats [47] and sinorphan actually reduced renin secretion in cirrhotic patients [48].…”
Section: Discussionmentioning
confidence: 87%
“…Dussaule et al (12) administered single oral doses of sinorphan to 16 patients with ascitic cirrhosis and observed increases in plasma ANP, a natriuretic response, a significant reduction of plasma renin activity, and no effects on arterial pressure. Park et al (36) observed that thiorphan caused natriuresis but did not alter cardiac output and systemic vascular resistance in cirrhotic rats. Neither study evaluated the effects of NEP inhibition on renal perfusion and free water metabolism, AVP plasma levels, and ANP urinary Fig.…”
Section: Discussionmentioning
confidence: 99%